The Development of the Assurance Relevance Interest Assessment Satisfaction (Arias) Collaborative Jigsaw Collaborative Learning Model in Writing News Text Class 8 Junior High School State 06 Medan - Siti Nurjanah; Syahnan Daulay; Khairil Ansari (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to determine (1) the process of developing a collaborative Jigsaw Cooperative Jigsaw Cooperative Assurance Relevance Interest Assessment (ARIAS) learning model in writing news texts (2) the results of the validation of the collaborative jigsaw cooperative Assurance Relevance Interest Assessment Satisfaction learning model (3) ) the effectiveness of learning outcomes that apply the collaborative Assurance Relevance Interest Assessment Satisfaction (ARIAS) learning model in jigsaw Cooperative in writing news texts by students of class VIII SMP Negeri 06 Medan. The test subjects consisted of material experts, design experts, Indonesian language study teachers, and VIII grade students of SMP Negeri 06 Medan. The results of this study indicate that (1) The results of the questionnaire needs that have been distributed can result that the respondent has never used a learning model that collaborates with other models, inspires confidence and is in accordance with student interests and students' assumption that news text material is too difficult and students feel confused organizing ideas when writing begins and find it difficult to arrange the first sentence in writing. (2) validation of material experts includes and validation of learning design experts. Validation in learning design get an average score of 89.02 gets very good criteria and validation results by material experts get an average score of 83.47 gets very good criteria (3) Test the effectiveness of learning products in the form of developing learning models of assurance relevance interest assessment satisfaction (ARIAS) Collaborative Jigsaw Cooperative of respondents 32 students consisting of 2 teachers of Indonesian Language and Literature studies who received an average of 80, 15% in the "very good" category. Students after using the development of the learning model Assurance Relevance Interest Assessment Satisfaction (ARIAS) collaborative jigsaw have improved learning outcomes compared to before using the development of the learning model of collaborative jigsaw cooperative assurance relevance interest assessment satisfaction (ARIAS). Thus the learning model Assurance Relevance Interest Assessment Satisfaction (ARIAS) collaborative cooperative jigsaw is more motivating, arouse students' self-confidence, independent and arises a sense of responsibility.